Dimerization of ABCG2 analysed by bimolecular fluorescence complementation - Haider, Ameena J.; Briggs, Deborah; Self, Tim J.; Chilvers, Hannah L.; Holliday, Nicholas D.; Kerr, Ian D. (Public Library of Science, 2011)
ABCG2 is one of three human ATP binding cassette transporters that are functionally capable of exporting a diverse range of substrates from cells. The physiological consequence of ABCG2 multidrug transport activity in leukaemia, and some solid tumours is the acquisition of cancer multidrug resistance. ABCG2 has a primary structure that infers that a minimal functional transporting unit would be a homodimer. Here we investigated the ability of a bimolecular fluorescence complementation approach to examine ABCG2 dimers, and to probe the role of individual amino acid substitutions in dimer formation. ABCG2 was tagged with fragments of venus fluorescent protein (vYFP), and this tagging did not perturb trafficking or function. Co-expression of two proteins bearing N-terminal and C-terminal fragments of YFP resulted in their association and detection of dimerization by fluorescence microscopy and flow cytometry. Point mutations in ABCG2 which may affect dimer formation were examined for alterations in the magnitude of fluorescence complementation signal. Bimolecular fluorescence complementation (BiFC) demonstrated specific ABCG2 dimer formation, but no changes in dimer formation, resulting from single amino acid substitutions, were detected by BiFC analysis.